Meteorological aspects of Salomon August Andrée's attempt to reach the North Pole by balloon in 1897 based on 20CR data - Etling, Dieter (Stuttgart : Gebrueder Borntraeger Verlagsbuchhandlung, 2017)
On 11 July 1897, a Swedish expedition under Salomon August Andrée attempted to reach the North Pole from Spitsbergen by balloon. The flight was terminated after only three days, as the weight of the balloon increased above a critical limit, due to an ice load caused by freezing fog and drizzle. Here the meteorological context of this expedition is discussed, in particular concerning the planning of the flight and in-flight weather conditions. Based on recently released pressure fields for the Arctic region for July 1897, obtained from the twentieth century reanalysis project (20CR), it can be shown that the Andrée expedition would not have reached the North Pole even with a perfect balloon, due to unfavourable wind conditions in the central Arctic after their departure from Spitsbergen.